Evaluation of Radiological and Functional Outcomes of Closed Complex Mid-shaft Tibia Fractures Treated with Primary Definitive All Wire Ilizarov Ring Fixator: A Prospective Study at Tertiary Care Centre of Nepal. - Gupta, Mithilesh Kumar; Panthee, Rajan; Yadav, Agam Kumar; Nepal, Santosh; Sah, Raj Kumar; Kafle, Gokul (Birat Journal of Health Sciences, 2024)
Introduction: Closed complex tibial shaft fractures are frequently encountered fractures in lower limb injuries. Various surgical methods for these fractures include primary or delayed fixation with intramedullary nails, minimal invasive plates, and primary definitive external stabilization using ring fixators. We conducted this study to evaluate the radiological and functional outcomes of primary definitive fixation of these fractures using an all-wire Ilizarov circular fixator. Objectives: The objectives of this study were to evaluate the radiological and functional outcomes of primary definitive fixation of closed complex tibial mid-shaft fractures in patients with compromised soft tissue status. Methodology: We defined Arbeitsgemeinschaft für Osteosynthesefragen/Orthopedic Trauma Association (AO/OTA) 42-B1 to AO/OTA 43-C3 fractures as complex tibial shaft fractures for this prospective observational study, and evaluated all 26 patients for the functional and radiographical progression according to ASAMI classification. Results: Twenty-six patients were stabilized with an all-wire circular ring fixator. The union time on average was 27.61 weeks. Among all patients, 7 (37.5%) cases had minor pin tract infections, and one (2.7%) patient landed a non-union, which required bone graft. Conclusion: With the use of an all-wire Ilizarov circular frame, there is a good mean time to union, fewer chances of re-operations, and good functional outcomes without any major complications.